Spatial, temporal and demographic patterns of cetacean strandings in the northcentral Gulf of Mexico - Russell, Mackenzie; Bloodgood, Jennifer; Carmichael, Ruth (J. Cetacean Res. Manage., 2022)
There are few published reports that summarise long‐term stranding data for cetaceans in the Gulf of Mexico (GoM). Cetacean stranding data from Alabama (AL) in the northcentral GoM have been recorded since 1978, with dedicated stranding response beginning in 1987, providing an opportunity to characterise spatial, temporal and demographic stranding patterns for this unique area, which links the eastern and western northern GoM coastline. To elucidate long‐term patterns, we analysed stranding records in AL from 1978–2018, taking into consideration the effects of periodic unusual mortality events (UMEs) on stranding demographics. During this 41‐year period, 774 stranding events were recorded involving at least 13 different cetacean species. Common bottlenose dolphins (Tursiops truncatus) were the most reported stranded cetacean (n = 692, 89.4%), followed by Stenella spp. (n = 31, 4.0%). Spatial analysis revealed three stranding hotspots for bottlenose dolphins and an additional hotspot for non‐bottlenose dolphin species that may represent a geographic influence in the northcentral GoM for strandings of offshore cetaceans. Because strandings were dominated by bottlenose dolphins, additional demographic analyses were possible for this species. Strandings occurred most often in the spring (March–May), and females and foetuses stranded more often in calving (January–April) than non‐calving season, consistent with increased mortality related to birthing or reproductive‐associated events. Subadults were found stranded more often than other size classes, indicating a potential stranding bias for this age class. These data are critical to guide future stranding response efforts, define vulnerable populations and help understand causes of mortality through time in the northcentral GoM. Our findings also highlight the importance of long‐term, consistent stranding response to enable identifying spatial and temporal trends that are necessary to support meaningful, range‐wide management and conservation.